Efeito da aminoguanidina e sua associação com metformina no sistema redox de ratos com diabetes tipo 2 e as implicações nos parâmetros bioquímicos e histológicos - Oliveira, Carla Miguel De (2021)
In a previous study, our group demonstrated that aminoguanidine (AG), a known inhibitor of Advanced Glycation End Products (AGEs), increased NOX2 (phagocytic NADPH Oxidase System) activity in rat peritoneal neutrophils, leading to increased activity phagocytic and neutrophil candicidal; however, this increase was less pronounced in diabetic rats. In this study, our aim was to investigate the role of AG in the redox balance in an experimental model of Type 2 Diabetes (DM2) and to evaluate its effect on the biochemical and histological parameters of these animals. Due to the molecular similarity of AG with metformin (MET), widely used in the treatment of DM2, we used here the two guanidines (AG and MET) and evaluated the effect of both, alone and/or associated, on the activity of pro and antioxidant enzymes and in biochemical and histological parameters. DM2 was induced in male Wistar rats through a hypercaloric diet, followed by intraperitoneal (IP) injection of streptozotocin (STZ) in low dosage (35 mg/kg). After confirmation of hyperglycemia, the animals were treated with AG and/or MET for 30 days and the parameters mentioned above were evaluated. Our results showed an increase in NOX 2 activity in the group treated with AG and/or MET regardless of the diabetic status, reinforcing previous results of our group. Regarding MPO, there was a decrease in enzymatic activity associated with hyperglycemia, and the different treatments had no effect on its activity. Related to the evaluation of oxidative stress markers, it can be noted that AG and MET demonstrated the ability to modulate oxidative metabolism, since the treatment with AG and MET was able to reestablish the activity of SOD, CAT and GPX, and decrease lipid peroxidation levels. In addition, in the biochemical profile, a better glycemic control was noted in the animals in the diabetic group MET and in the group treated with gliclazide, demonstrating the effectiveness of the DM2 model standardized in this study. In the lipid profile, there was no change in the levels of total cholesterol and HDL cholesterol due to hyperglycemia. However, groups treated with AG and/or MET showed a decrease in triglyceride levels. It can also be noted that there was an increase in AST and ALT resulting from the diabetic state. Nevertheless, in the groups treated with AG and MET, there was a decrease in AST and ALT, demonstrating the ability of the compounds to recover from liver damage. Alkaline phosphatase was increased by hyperglycemia, however, treatments with AG and MET did not affect this parameter. Serum markers of renal function, urea and creatinine, were not affected by the treatments. Through histological analysis it was noted that AG and MET alone or in association had beneficial effects by minimizing liver and kidney damage arising from DM2. Thus, we concluded that treatment with AG, MET and the association of these compounds induced an improvement in the liver parameters of diabetic animals, decreased triglyceride levels, restitution of SOD, CAT and GPX activity, and was able to promote an improvement in kidney and liver tissue damage. Given the above, it can be noted that the association of AG and MET acted beneficially in this experimental model, requiring further studies to establish whether the association of guanidines can bring more benefits than the isolated action of metformin, widely used in DM2 treatment.